2015
DOI: 10.1208/s12249-015-0468-9
|View full text |Cite
|
Sign up to set email alerts
|

Double-Layered Matrix of Shellac Wax-Lutrol in Controlled Dual Drug Release

Abstract: Abstract. Double-layered matrix tablets prepared from shellac wax-lutrol were fabricated using a molding technique, and the release of hydrochlorothiazide and propranolol HCl from the inner tablet or outer layer was studied. The simultaneous determination of dual drug release was measured with first derivative UV spectrophotometry. The tablet containing shellac wax as the outer tablet and lutrol as the inner tablet showed more appropriate drug release and the size of the inner layer influenced the rate of drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The release of hydrophilic propranolol hydrochloride in a dual drug formulation (propranolol hydrochloride and hydrochlorothiazide) with a 7:3 ratio of lutrol to shellac was slower than that of the individual drug formulation, which can be attributed to the addition of the hydrophobic hydrochlorothiazide that increased the strength of the gel in the tablet . Further research suggested that the components and the surface area affect the drug release behavior of double-layered matrix tablets . As shown in Figure B, double-layer matrix tablets with an erodible inner drug-loaded layer and an erodible outer layer exhibited biphasic drug release.…”
Section: Shellac-based Delivery Systemsmentioning
confidence: 98%
See 4 more Smart Citations
“…The release of hydrophilic propranolol hydrochloride in a dual drug formulation (propranolol hydrochloride and hydrochlorothiazide) with a 7:3 ratio of lutrol to shellac was slower than that of the individual drug formulation, which can be attributed to the addition of the hydrophobic hydrochlorothiazide that increased the strength of the gel in the tablet . Further research suggested that the components and the surface area affect the drug release behavior of double-layered matrix tablets . As shown in Figure B, double-layer matrix tablets with an erodible inner drug-loaded layer and an erodible outer layer exhibited biphasic drug release.…”
Section: Shellac-based Delivery Systemsmentioning
confidence: 98%
“…However, the drug release of matrix tablets with an insoluble outer layer and an erodible inner drug-loaded layer followed zero-order kinetics owing to the unexposed inner surface area. Outer drug-loaded matrix tablets performed faster drug release than the inner drug-loaded matrix tablets and did not exhibit biphasic drug release …”
Section: Shellac-based Delivery Systemsmentioning
confidence: 98%
See 3 more Smart Citations